BAHASA SLOGAN PADA MEDIA SPANDUK DI LINGKUNGAN KAMPUS UNIVERSITAS BANTARA SUKOHARJO: PERSPEKTIF IDEOLOGI GRAMATIKA - Sudiyana, Benedictus (Universitas Ahmad Dahlan, 2015)
The aims of these research are about the language slogan at the banner media in the Campus Area of Veteran Bangun Nusantara University of Sukoharjo are (a) to describe the language slogan using the thematic acpects, (b) to describe the language slogan constructing the grammatical based on ideological perspectives: (i) transitivity, (ii) active passive forms, (iii) positive-negative forms, (iv) declarative, interrogative, imperative modus, (v) relational modality, (vi) personal pronoun, and (vii) expressive modality. This research uses the qualitative approach. Data are the slogan texts in the Veteran Bangun Nusantara University of Sukoharjo, at, February to June 2014. Data are text units. Data collecting instrument is the matrix form for the data generating. Data analysis uses the inventory, classify, and reflect-interpretative procedures. The result can be concluded (1) the language slogan at the banner media in the area of Veteran Bantara University of Sukoharjo from the thematic perspective addressed to the universal character public; (2) the language slogan constructed from the grammatical based on ideological perspectives (a) the transitivity systems are from the process, participant, and circumstance aspects indicate that textual effect is not strict in the actional language; (b) the choice active passive sentence compress to value of sympatic responses to natural procedural based on passive position; (c) the choice of active passive sentence indicates the strict of admission; (d) the choice of declarative modus(indicative)gives the practical expressive of authoritative power; (e) the choice of relational modality appears to the expression of obligation; (f) the choice of pronominal persona uses mechanical utensils of non ideogical, the ideology also to get on solidarity-inclusive ideological, (g) the choice of expression modality shows certainty for a reality proposition